Effects of psychosocial interventions on self‐efficacy of dementia caregivers: a literature review. (9th September 2015) - Tang, Wai Kit; Chan, Chung Yan Joanne
Abstract : Introduction: Self‐efficacy plays an important role in mediating stressors and physical and psychological outcomes in dementia caregiving. Objectives: This literature review aims to identify, summarize, and critically appraise current evidence on the psychosocial interventions used for enhancing the self‐efficacy of caregivers of patients with dementia (PWD). Methods: A database search from two major web gateways was conducted to identify relevant research articles with an intervention for caregivers of patients with any type of dementia that included self‐efficacy as an outcome measure. Results: A total of 14 studies met the criteria. The key findings and characteristics of the interventions were summarized and analyzed. The results showed that caregivers' self‐efficacy and other aspects could be improved by psychosocial interventions. Conclusion: The efficacy of the interventions for self‐efficacy and other outcomes for caregivers and PWD were explored. Recommendations on the effects and significance of various psychosocial interventions for caregivers of PWD in enhancing self‐efficacy were discussed. Copyright © 2015 John Wiley & Sons, Ltd.